Simulação computacional, projeto, construção e análise do desempenho de uma matriz para extrusão em canal angular dedicada ao processamento de chapas - Springer, Phillip (2012)
The present work describes the design, construction and testing of an equal channel angular pressing (ECAP) die characterized by rectangular cross section channels. The main parameter of the ECAP dies is the geometry of the channels, given by the angle trough which they meet, and the curvature radii at this point. The material employed in the experiments was an Al AA1050, 7 mm thick plate. The main motivation of the project is to produce the tooling necessary for the production of samples to be employed in future studies, directed to the crystallographic texture change of the above named material so as to improve its deep drawing behavior. Indeed, there are indications that both asymmetrical rolling and ECAP processing can minimize unfavorable textures. This present investigation is composed by two sequential and complementary subprojects: (i) Numerical analysis by finite elements (FEM) of the simultaneous and independent variation of the external (R) and internal (r) curvature radii at the channels intersection, plus experimental validation, a procedure that seeks to minimize the deformation heterogeneity of the billet. Using a Pb-62% alloy twelve R-r combinations were tested and simulated, keeping constant the angle at the channels intersection. Also, the phenomenon known as "corner gap" (a detachment of the billet from the outer channel wall) was analyzed and its influence on the billet equivalent deformation determined. (ii) From the results obtained on subproject (i), and additional considerations, an ECAP die for flat billet processing was designed and constructed HAVING R =3 AND r = 0. Using FEM simulation the equivalent strain distribution was mapped for plates subjected to one and four passes. Experimental validation of such maps was carried out employing Vickers microhardness measurements of the viii plate cross section. The evolution of the tensile properties and grain size confirmed the good performance of the ECAP die design.